Wear analysis of unicondylar mobile bearing and fixed bearing knee systems: A knee simulator study - Kretzer, Jan Philippe; Jakubowitz, Eike; Reinders, Jörn; Lietz, Eva; Moradi, Babak; Hofmann, Kerstin; Sonntag, Robert (Acta biomaterialia, 2011)
Unicondylar knee arthroplasty is an attractive alternative to total knee arthroplasty for selected patients with osteoarthritis. Mobile bearing knee designs have been developed to improve knee kinematics, lower contact stresses and reduced wear of ultra-high molecular weight polyethylene compared with fixed bearing designs. This study compared in vitro wear behavior of fixed and mobile unicondylar bearing designs. Analysis was performed using a force-controlled AMTI knee simulator according to ISO 14243-1:2002(E). The wear volume of the implants was determined gravimetrically. Optical surface characterization and an estimation of wear particle size and morphology were performed. Implant kinematic data for both designs were determined. The wear rates averaged 10.7±0.59mg per 106 cycles for the medial and 5.38±0.63mg per 106 cycles for the lateral components of the mobile bearings, compared with 7.51±0.29mg per 106 cycles and 3.04±0.35mg per 106 cycles for the fixed bearings. The mobile bearings therefore exhibited higher wear rates (P<0.01) compared with the fixed bearings. The tibial polyethylene inserts of the mobile bearings showed pronounced backside wear at the inferior surface. The kinematics of both designs was similar. However, anterior-posterior translation was lower in the mobile bearings. The wear particles were mainly elongated and small in size for both designs (P=0.462). This study shows that wear may play an important role in unicondylar mobile bearing knee designs. Advantages of unicondylar mobile designs compared with fixed bearing designs, which have been proposed in terms of wear behavior and improved kinematics, could not be confirmed.
Available online 29 September 2010
Gesehen am 11.07.2022